Radiation risk factors in incidence anortality among exposed individuals of East Kazakhstand m - Kazbek Apsalikov; Talgat Muldagaliev; Rustem Apsalikov; Shinar Serikkankyzy; Zaure Zholambaeva (Central Asian Journal of Global Health, 2014)
Introduction: Lengthy clinical and epidemiological studies at the Research Institute of Radiation Medicine and Ecology have discovered basic patterns of long-term effects from ionizing radiation in population groups exposed to radiation risk. Methodology for calculating injury from radiation risk factors has been developed and implemented to minimize the effects of the Semipalatinsk nuclear test site (SNTS). Material and methods: We analyzed materials from the database of the Scientific Medical Register that were exposed to radiation as a result of SNTS. We analyzed both male and female populations of the Abay, Beskaragai and Zhanasemei, Kokpekti (control) areas of East-Kazakhstan region (EKR) from 2008-2012. These populations were split into three groups allocated by the generation. The first group represented persons born from the period of 01/01/1930 -08/01/1949 and their children born from the period of 10/09/1949-12/31/1962. The second group were persons born after 01/01/1963. The third group served as the control and were persons who immigrated to these areas after 1990. Results: There was an increased incidence of cancer (21.5%, p < 0.000734), cardiovascular diseases (10.2%); respiratory problems (9.6%), gastrointestinal issues (9.1%, p < 0.00371-0.00679) in the first group. The effect of the radiation dose has not been fully stuided among the subjects in the second group.